Klasifikasi Tumbuhan Obat Berdasarkan Citra Daun Menggunakan Algoritma CNN - Sinaga, Nicolas Novelico; Sembiring, Arnes (INCODING: Journal of Informatics and Computer Science Engineering, 2025)
This study aims to classify various types of medicinal plants based on leaf images by utilizing the Convolutional Neural Network (CNN) algorithm. The model used is the MobileNetV2 architecture because of its ability to balance accuracy and computational efficiency. The leaf images dataset is divided into training and validation data, then processed through several stages such as augmentation, fine-tuning, and regularization. The evaluation results show that the model successfully achieved the highest validation accuracy of 98,43%, proving that this approach is effective in identifying types of medicinal plants.